Pemberdayaan Masyarakat Melalui Pengolahan Produk Turunan Limbah Kulit Kopi di Desa Pace, Silo, Jember - Nindha Ayu Berlianti; Muhammad Iqbal Mukhlis; Nufusul A'ilah; Adam Hadi Surya; Alvines Jihan Putri Susanggita; Rara Mareta Hartini Ningrum (Jurnal Pemberdayaan Masyarakat, 2026)
Coffee is a crucial commodity for Indonesia, particularly in the smallholder plantation sector. However, coffee husks often lead to environmental pollution. This study focuses on processing coffee husks into briquettes as an eco-friendly alternative fuel and a potential economic benefit. The briquette production process starts with the collection and drying of coffee husks, followed by roasting, grinding, and mixing with binders such as tapioca. The resulting briquettes are packaged in a functional design to facilitate distribution and enhance burning efficiency. This community service program involves farmer groups in Pace Village, Silo District, Jember Regency, East Java, using the methods of identifying needs, training, and making briquette prototypes. The results show that coffee husk briquettes are not only effective in reducing waste but also provide economic benefits such as additional income for farmers and micro-business opportunities. Furthermore, these briquettes contribute to deforestation reduction and lower carbon emissions. With proper training and support, coffee husk briquette production can become a small industry that supports the local economy and improves community welfare.